Judicial Jurisdiction in Resolving Disputes Arising from Professional Sports Contracts - Jararweh , Ammar; Obeidat, Yusuf Mohammed Gassim (Legality : Jurnal Ilmiah Hukum, 2026)
This study addresses and eliminates manifestations of injustice in professional sports contracts by examining the judicial jurisdiction for resolving disputes arising from professional sports contract. The sports contract governs the legal relationship between a professional football player and a sports club. Like other contractual relationships, it is susceptible to disputes, both during implementation and after termination. The resolution of such disputes is typically handled by the legal committees affiliated with both national and international sports federations. Non-compliance by players and clubs entails disciplinary sanctions. This has created a competitive situation between the sports bodies responsible for resolving sports contract disputes and the jurisdiction of national courts. Therefore, this study aims to examine the judicial jurisdiction of legal committees of national and international sports associations, and to evaluate the extent of ordinary national courts’ jurisdiction over disputes arising from professional football contracts. The study concludes that it is essential to attain a balance between the independence of sports bodies in resolving contractual sports disputes and the legal rights of individuals under their national laws.